2021
DOI: 10.31234/osf.io/2jsdg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The relative balance between languages predicts the magnitude of whole-language inhibition.

Abstract: After naming pictures in their second language (L2), bilinguals experience difficulty in naming pictures in their native language (L1). The “L2 after-effect” is a lingering consequence of inhibition applied to L1 to facilitate L2 production. We proposed that the amount of L1 inhibition depends on the relative balance between current activation of L1 and L2. In two experiments, bilinguals performed a blocked picture-naming task which provided a measure of the relative balance between the two languages and index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Yet, further theoretical refinement has dissected the rather broad notion of inhibition and linked it to different levels of selection. It has been assumed that there is a more global inhibition acting on the lexical level (i.e., making all particles of a language less accessible), which is linked to the notion of reversed language dominance ( Green, 1998 , but see also Casado et al, 2021 ). More in line with recent suggestions ( Casado et al, 2021 ), our findings do not reveal consistent evidence for the reversed language dominance effects as support for the notion of global lexical level inhibition probably because of a missing assessment of current language dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, further theoretical refinement has dissected the rather broad notion of inhibition and linked it to different levels of selection. It has been assumed that there is a more global inhibition acting on the lexical level (i.e., making all particles of a language less accessible), which is linked to the notion of reversed language dominance ( Green, 1998 , but see also Casado et al, 2021 ). More in line with recent suggestions ( Casado et al, 2021 ), our findings do not reveal consistent evidence for the reversed language dominance effects as support for the notion of global lexical level inhibition probably because of a missing assessment of current language dominance.…”
Section: Discussionmentioning
confidence: 99%
“…This would explain why their L1 could have been more readily activated when compared to the L1 of English-Chinese bilinguals, facilitating the processing of congruent L2 binomials. This account is compatible with the extended Inhibitory Control model that is based on the language balance model (Casado, et al, 2021), which holds that the amount of inhibition applied to L1 during L2 use is related to the relative balance between the two languages. Studies have shown that when the two languages of a bilingual speaker are relatively balanced, the switching costs between languages becomes comparable, i.e., symmetrical switching costs (Christoffels et al, 2007;Declerck et al, 2013;Schwieter & Sunderman, 2008).…”
Section: L1 Inhibitionsupporting
confidence: 63%
“…In blocked picture naming tasks, asymmetries have been observed with respect to language order. Naming first in the dominant language facilitates later naming in a non-dominant language (Branzi et al, 2014;Casado et al, 2022;Misra et al, 2012;Wodniecka et al, 2020); by contrast, no such facilitation occurs for the dominant language following a prior block of naming in a non-dominant language. Both new and repeated words in the L1 show interference when preceded by naming in the L2.…”
Section: Language Directionmentioning
confidence: 94%
“…Switch costs have also been demonstrated in blocked languageswitching paradigms in which the response language changes between blocks of stimuli (Branzi et al, 2014;Casado et al, 2022;Degani et al, 2020;Kleinman & Gollan, 2018;Misra et al, 2012;Wodniecka et al, 2020). It is worth noting that such effects are not confined to translation equivalents: naming any pictures in one language can interfere with lexical access in another, although in some cases naming translation equivalents incurs a greater cost (e.g., Kleinman & Gollan, 2018).…”
Section: Evidence For Interferencementioning
confidence: 98%